Induction of apoptosis in human lymphoblastoid cells by kaempferol 3‐O‐β‐isorhamninoside and rhamnocitrin 3‐O‐β‐isorhamninoside from Rhamnus alaternus L. (Rhamnaceae) - Bhouri, W. (Cell Prolif, 2011)
Objective:  Kaempferol 3‐O‐β‐isorhamninoside (K3O‐ir) and rhamnocitrin 3‐O‐β‐isorhamninoside (R3O‐ir) from Rhamnus alaternus L leaves are investigated for their ability to induce apoptosis in human lymphoblastoid cells. We have attempted to characterize apoptotic pathway activated by these two flavonoids. Material and methods:  Apoptosis of the human TK6 lymphoblastoid cell line was detected by DNA fragmentation, PARP cleavage and by evaluating caspase activity. Results:  Apoptosis was observed after 24‐ and 48‐h incubation of the cells with the tested compounds. DNA fragmentation was observed after treatment with flavonoids; this was confirmed by demonstration of PARP cleavage. Caspase‐3 and caspase‐8 activities were induced by both K3O‐ir and R3O‐ir flavonoids showing highest activity with compound concentration of 400 μg/ml. Conclusion:  We have demonstrated that K3O‐ir and R3O‐ir induce apoptosis in human lymphoblastoid cells by the extrinsic pathway of apoptosis.